O orçamento participativo em face dos dilemas teóricos e práticos da democracia contemporânea: uma comparação das experiências de Belo Horizonte e Porto Alegre - Neimar Duarte de Azevedo (2012)
This PhD dissertation is embedded in the debate on the relations of participation and representation within the institutional arrangements aimed at broadening citizenship participation. It's main aim is of verifying whether the decision-making process inaugurated by Participatory Budgeting is beyond the scope of the theoretical foundations of canonical contemporary democratic theory. To facilitate this analysis it was necessary to identify the elements that make up the decision process of participatory budgeting and compare them with the state of the art of democratic theory, having as the principal reference the theory of polyarchic democracy developed by Robert Dahl. As empirical element were studied the experiences of Porto Alegre and Belo Horizonte. It was found that participatory budgeting can be legitimized by the theoretical foundations of representative democracy and that this institutional arrangement exemplifies the interdependence present in the relationship between participation and representation, fulcrum of contemporary democracy. It was evident, too, the importance of political participation of citizens, especially at subnational levels of government to enhance democracy at the present time due to the expansion of the size of democratic regimes. However, participation ensured by experiences as participatory budgeting is limited by an institutional representative entered into the system. In this sense, citizens who participate in these decisory spaces play the role of representatives in an analogous way to that of political party representation, but play this role as a mechanism to enable a decision-making process toward the expansion of political participation and democratization of public management.